North-West Russia in the context of European integration - Kochegarova, Tamara; Simonyan, Renald (Baltic Region, 2013)
Integration is one of the main consequences of globalization. Elements of microsystems are growing closer, which brings to the foreground problems of interaction and — in a longer perspective — those of close cooperation between different social systems. The article considers the case of North-West Russia, the only territory having a common border with the EU, in order to examine the issue of Russia using the geographical factor, which Otto von Bismarck called the most powerful and intrinsic factor in history. The significance of this factor increased after the Cold War. It was then when the independent Baltic States became a platform for emergence and recognition of the Baltic Sea region. The author focuses on the social and cultural integrity of the region and considers the traditional Nordic countries and the Baltic Sea states as interrelated components of a single region, different from other European regions in terms of economic interests, as well as its natural and sociocultural landscape.